(untitled) (Patan Pragya, 2023)
Situated at the southeast corner of Basantapur ḍabalī in Kathmandu, a small shrine and stone caitya, collectively referred to as Basantapur Bahāḥ or Deśasumantra vihāra by certain scholars. However, the origins of these designations lack scholarly citation. The structural integrity of the site remained robust until the seismic earthquake of 1990 V.S. An inscription on the shrine’s eastern exterior attributes its establishment to Bhavani Śaṅkara Baniyā’s residence. Bhavani Śaṅkara Baniyā initiated the installation of an Akṣobhya Buddha image within his dwelling in 866 N.S. Another likeness of Akṣobhya Buddha found placement at Rāj Kula Bahi. Along with this philanthropic act, Bhavani Śaṅkara stipulated the annual worship of Kvāpādyaḥ at Rāj Kula Bahi on Kartika Purnima, financed by the income from his endowed properties. Post-donation, the property seamlessly merged into Sikhamu Bahāḥ, a subsidiary branch of the larger religious complex, subsequently known as Baniyā vihāra. Unfortunately, the seismic event of 1990 V. S. left the structure in ruins, with no subsequent reconstruction efforts. Sole remnants include the preserved Akṣobhya images and the enduring caitya.